2017
DOI: 10.1145/2996188
|View full text |Cite
|
Sign up to set email alerts
|

Show Me You Care

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Most of the research on empathy detection has focused on spoken conversations or interactions, some in online platforms (e.g. (Pérez-Rosas et al, 2017;Khanpour et al, 2017;Otterbacher et al, 2017;Sharma et al, 2021;Hosseini and Caragea, 2021), very little on narrative genre (Buechel et al, 2018;Wambsganss et al, 2021), and even less in clinical settings. Buechel et al (2018) used crowdsourced workers to self-report their empathy and distress levels and to write empathic reactions to news stories.…”
Section: Related Workmentioning
confidence: 99%
“…Most of the research on empathy detection has focused on spoken conversations or interactions, some in online platforms (e.g. (Pérez-Rosas et al, 2017;Khanpour et al, 2017;Otterbacher et al, 2017;Sharma et al, 2021;Hosseini and Caragea, 2021), very little on narrative genre (Buechel et al, 2018;Wambsganss et al, 2021), and even less in clinical settings. Buechel et al (2018) used crowdsourced workers to self-report their empathy and distress levels and to write empathic reactions to news stories.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, use to emotionalize, informal and less complex language styles can positively influence consumer engagement. Otterbacher et al, (2017) found that informal communication styles can be used to soften hierarchical power relations, reduce social distance, and convey a sense of intimacy.…”
Section: Language Stylementioning
confidence: 99%
“…Most of the research on empathy detection has focused on conversations or interactions, as dialogue systems Chen et al, 2022a;Samad et al, 2022), or in online platforms (e.g. (Pérez-Rosas et al, 2017;Khanpour et al, 2017;Otterbacher et al, 2017;Sharma et al, 2020;Lahnala et al, 2022;Sharma et al, 2021;Hosseini and Caragea, 2021), a few on news stories and other narratives (Buechel et al, 2018;Wambsganss et al, 2021b;Sedoc et al, 2020;Mundra et al, 2021;Guda et al, 2021), and even less on empathy in clinical settings Shi et al, 2021). Buechel et al (2018) used crowd-sourced workers to self-report their empathy and distress levels and to write empathic reactions to news stories.…”
Section: Related Workmentioning
confidence: 99%